Review: Clinical, genetic and neuroimaging features of frontotemporal dementia. (21st January 2019) - Convery, R.; Mead, S.; Rohrer, J. D.
Abstract : Frontotemporal dementia (FTD) is a heterogeneous group of disorders causing neurodegeneration within a network of areas centred on the frontal and temporal lobes. Clinically, patients present with behavioural symptoms (behavioural variant FTD) or language disturbance (primary progressive aphasia), although there is an overlap with motor neurone disease and atypical parkinsonian disorders. Whilst neuroimaging commonly reveals abnormalities in the frontal and temporal lobes, a closer review identifies a more complex picture with variable asymmetry of neuronal loss, widespread subcortical involvement and in many cases more posterior cortical atrophy. An autosomal‐dominant genetic disorder is found in around a third of people with mutations in progranulin, C9orf72 and the microtubule‐associated protein tau being the commonest causes. In the other two‐thirds, the disorder is sporadic, although recent genome‐wide association studies have started to identify genetic risk factors within this group. Much of this knowledge has been understood only in the past 10 years and so this review will discuss the current knowledge about the clinical, genetic and neuroimaging features of FTD.